The Effect of Providing Basic Life Support Materials Using the Audiovisual Method on the Knowledge and Skills of Cardiopulmonary Resuscitation - Bayu Aji Sadewa; Angela Puspita; R. Varidianto Yudo Tjahjono; Titut Harnanik (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cardiac arrest is a leading cause of death worldwide, including in the United States and Indonesia, with most cases triggered by coronary heart disease. Successful resuscitation largely depends on rapid interventions such as cardiopulmonary resuscitation (CPR) and defibrillation, as survival chances decrease by approximately 10% for every minute without intervention. Basic Life Support (BLS) has been proven to improve resuscitation outcomes; however, knowledge and skills related to BLS remain limited, including among medical students. This study aimed to analyze the effect of providing BLS training using audiovisual methods on the knowledge and skills of students who are members of the Medical Assistance Team (Tim Bantuan Medis/TBM), Faculty of Medicine, Universitas Hang Tuah Surabaya, in performing cardiopulmonary resuscitation (CPR). A cross-sectional study was conducted at the Faculty of Medicine, Universitas Hang Tuah, Surabaya, Indonesia, from June to September 2025. A total of 21 TBM students were selected using a total sampling technique. The dependent variables were knowledge and skills in performing CPR, while the independent variable was BLS training delivered using audiovisual methods. Data were collected using questionnaires that had been tested for validity and reliability. Data analysis was performed using the Wilcoxon signed-rank test for knowledge levels and the McNemar test for CPR skills. The Wilcoxon signed-rank test showed that knowledge levels were significantly improved after the provision of BLS training using audiovisual methods (p = 0.020). The McNemar test demonstrated that CPR skills were also significantly improved after the audiovisual BLS training (p = 0.008). There is a significant effect of audiovisual-based Basic Life Support (BLS) training on improving both CPR knowledge and skills among TBM students.